THEORY OF ACCEPTANCE MODEL UNTUK EVALUASI PERILAKU PENGGUNA SISTEM INFORMASI DI PERGURUAN TINGGI (STUDI KASUS: ASMI CITRA NUSANTARA DI BANJARMASIN) - Muhammad Fahmi (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2021)
Various advantages of Information System technology in Universities encourage the use of Information Systems in Universities, until now it has become a necessity no longer a necessity or compulsion for an institution. Utilization of Information Systems in Universities as information centers can be one of the strategies to develop the level of education. This research aims to find out the picture of the successful application of Information System technology in universities as an information center based on user evaluation in the campus environment of ASMI Citra Nusantara Banjarmasin. Evaluation can predict the level of utilization of technology in the future. The method used in the study was a survey with 158 research samples with the Theory of Acceptance Model approach analyzed using the Partial Least Square technique. The results showed that all proposed hypotheses were acceptable so that the variables in the Theory of Acceptance Model could describe user attitudes in information system evaluation. This research can be one of the reviews that shows that the Theory of Acceptance Model as the right model for quantitative-based Information System evaluation research and case studies. This study concludes that the Theory of Acceptance Model is relevant in determining and assessing user behavior regarding the use of technology